DEFECTS IN ALUMINUM THIN FILMS DEPOSITED ON PET SUBSTRATE AND THEIR FORMATION MECHANISM - Kobayashi, T.; Yoshifumi, I.; Utsumi, Y.; Kanematsu, H. (Journal of Advanced Manufacturing Technology (JAMT), 2019)
Defects in aluminum films deposited on PET substrate by a vacuum web coater were investigated to clarify their formation mechanisms. The defects detected by optical transmission equipment were taken from a plastic web, and then observed with optical and scanning electron microscopes (SEM). Subsequently, the shapes were classified into four types: teardrop, splashing, scattered dots and round. However, the features of the microstructure were classified as follows: Clear boundary line without films; Unclear boundary line with transparent films; Unclear boundary line with transparent films and residual particles at the center and thermally damaged and penetrated. It has been suggested that the defect formation mechanisms are as follows: (a) splashing of molten aluminum droplets, (b) oxidation of aluminum due to oxygen-containing substances such as water and oil and (c) oxidation of aluminum due to the adhesion of polymer lint.